Psychological Intrusion – An Overlooked Aspect of Dental Fear - Chapman, Helen R.; Kirby-Turner, Nick (Frontiers in Psychology, 2018)
Dental fear/anxiety is a widely recognised problem affecting a large proportion of the population. It can result in avoidance and/or difficulty accepting dental care. We believe that psychological intrusion may play a role in the aetiology and maintenance of dental fear for at least some individuals. In this narrative review we will take a developmental perspective in order to understand the its impact across the lifespan. We will consider the nature of ‘self’, parenting styles, the details of intrusive parenting or parental psychological control, and briefly touch upon child temperament and parental anxiety. Finally, we draw together the supporting (largely unrecognised) evidence available in the dental literature. We illustrate the paper with clinical examples and discuss possibly effective ways of addressing the problem. We conclude that psychological intrusion appears to play an important role in dental fear, for at least some individuals, and we call for detailed research into the extent and exact nature of the problem. A simple means of identifying individuals who are vulnerable to psychological intrusion would be useful for dentists.